Risk factors for acute respiratory infection (ARI) in children under five years of age - M Nabil Azkia Mastera; Muhammad Naswir; Hendra Dhermawan Sitanggang; Dwi Noerjoedianto (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Acute Respiratory Infection (ARI) remains one of the major health problems among children under five in Indonesia. The high incidence of ARI is influenced by various factors, including nutritional status, housing conditions, and previous history of ARI. Purpose: to determine the risk factors associated with ARI among children under five years of age. Method: This research used a quantitative method with a cross-sectional design. The sample consisted of 81 children under five selected using purposive sampling technique. Data were collected through questionnaires, observations, and medical records, then analyzed using the Chi-Square test with a 95% confidence level. Results: The results showed that there was a significant relationship between nutritional status and the incidence of ARI among children under five (p-value = 0.004; PR = 2.297; 95% CI = 1.287–4.098). In addition, a history of ARI was also significantly associated with the incidence of ARI (p-value = 0.000; PR = 13.000; 95% CI = 5.048-33.476). Meanwhile, residential density was not significantly associated with ARI incidence among children under five (p-value = 0.474). Conclusion: In conclusion, nutritional status and history of ARI are risk factors associated with ARI incidence among children under five. Suggestion: Therefore, efforts are needed to improve nutritional status, implement clean and healthy living behaviors, and conduct regular health monitoring to prevent recurrent ARI among children under five.